Oral and Oropharyngeal Cancer in Mosul City in 2005 - Hadeel S Alazzawi; Ayad H Al-Ramadhani (University of Mosul, College of Dentistry, 2009)
Aim: To evaluate oral cancer status in Mosul during 2005 that will help planning research, prevention,and treatment measures. Materials and Methods: Data on oral cancer cases treated in Mosul cityhospitals during 2005 were collected. These cases included patients who were residents in Mosul cityonly. The study covers the site, clinical presentation, histopathological, and methods of treatment offore mentioned malignancy. Results: Thirty one new cases diagnosed in Mosul hospitals wereincluded in this study. The Male to female ratio was 2.4:1. About 58% of patients were over sixty yearsof age. The most common site affected the lip (22.6%). Histologically, squamous cell carcinoma wasthe most common representing 64.5% of cases examined. Metastasis to regional lymph nodes waspresent in 74.2% of cases. Conclusion: In Mosul, oral cancer is rare. The cases of this study weredetected in advanced stages affecting the choice of therapy and making prognosis much worse